Analysis of Absorbing Aerosols for Ground-Based Astronomical Observatories in Türkiye - Fethullah Polat; Kazım Kaba; Sima Aydın (Journal of Anatolian Physics and Astronomy, 2025)
In this study, the impact of aerosols on ground-based astronomical observations in Türkiye was examined, and their spatial and temporal variations were assessed. Satellite data was used in the study due to its advantage of wide area coverage. The absorbing aerosol index (AAI) product, derived from multi-sensor observations, was utilized in the research.Positive AAI (PAAI) is a measurement of the concentration of absorbing aerosols (such as dust, smoke, volcanic ash, etc.) in the atmosphere. High PAAI values are often indicative of significant weather events, such as dust storms, forest fires, and volcanic eruptions. Therefore, PAAI values serve as an important indicator for atmospheric conditions affecting astronomical observations.The study revealed the current aerosol characteristics of the observatories in detail. The global average PAAI value for 2024 is calculated to be 0.34, which is lower than the 45-year long-term global average of 0.38. However, the average PAAI value for Türkiye in 2024 is 0.38, which is consistent with the long-term global average.These findings indicate that the observatories in Türkiye are closely aligned with the global average aerosol conditions. The results provide significant insights into the evaluation of astronomical observation data accuracy, the planning of observation programs, and the selection of suitable observation sites. Understanding the impact of atmospheric aerosols on photometric and spectroscopic data is critical for improving the success of future high-precision astronomical observations.